全身FDG-PET撮像における診断用造影CT画像を用いた減弱補正の妥当性 - 坂本, 攝; 村瀬, 研也; 中本, 裕士; 千田, 道雄; 松本, 圭一 (日本放射線技術学会雑誌, 2007)
Objective: Image fusion has been recognized as a useful technique in diagnostic imaging. We have been evaluating the manual image fusion of PET and contrast-enhanced (CE) CT obtained separately. The CT images can be used for attenuation correction as well as for image fusion; however, the quantitative accuracy of CT-corrected PET images has yet to be assessed. The purpose of this study was to compare the radioactivity concentration between conventional 68Ge-corrected and CECT-corrected PET images. Methods: Twenty patients underwent a whole-body PET scan, followed by a CT scan with intravenous contrast material, after careful positioning using an individually molded vacuum cushion. Two different attenuation-corrected emission data sets were produced, i.e., 68Ge-corrected images and CECT-corrected images. Image registration was performed by maximizing mutual information-based cost function, between the CT and the combination of emission and transmission PET volumes. The CT pixel values in Hounsfield units were transformed into linear attenuation coefficients in cm−1, using a conversion formula for a lookup-table from phantom experiments. Measured activity concentrations from identical regions of interest in representative normal organs and in 25 pathologic foci of uptake were compared. In addition, the quality of the reconstructed images was assessed using the normal mean square error (NMSE). Results: Measured average radioactivity concentrations were 1.38-9.56% higher for CECT-corrected images than for 68Ge-corrected images. Overall, the NMSE value of CECT-corrected images compared with 68Ge-corrected images was 0.02±0.01. Conclusions: The difference in quantitative values between 68Ge-corrected and CECT-corrected PET images was comparable to that of an integrated PET/CT system. Diagnostic CT images with intravenous contrast performed separately before or after a PET scan could be used clinically not only for fusion but also for attenuation correction.